Images of Islam and Muslim in v.s Naipaul's travel writing - Abdullah, Nurul 'Ain; Hasan, Md. Mahmudul (IIUM Press, International Islamic University Malaysia, 2017)
The Nobel laureate V. S. Naipaul (1932 –) has made extensive comments on Islam and its adherents in his two widely circulated travel writings, Among the Believers: An Islamic Journey (1981) and Beyond Belief: Islamic Excursions among the Converted Peoples (1998). These two works have triggered debates about his representation of Muslims, as it is believed that his treatment of Islam and its believers evinces his limited perspective on them. Under the surface of his gentlemanlike ways of listening and retelling the stories of the people he met in the Muslim countries he visited, his tendency to judge and caricature is palpable in these two books. It seems that he visited the four countries – Indonesia, Iran, Malaysia and Pakistan – and wrote the two books only to reinforce his distorted, preconceived notions and ideas about Islam. In other words, his travels are only to find evidences to vindicate his negative assumptions he held about Islam and Muslims. Omitting facts that do not suit his tendency to caricature, he fails to provide a balanced and unbiased representation of the countries and the people he encountered. Based on these premises, we aim to investigate Naipaul’s portrayal of Islam and Muslims in the two books mentioned and seek to differentiate the cultural and individual practices – that are put forth as Islamic by Naipaul – from normative, actual Islamic teachings. The author’s neo-Orientalist tendencies as well as his strategy of surveillance will be discussed, and his standing as a postcolonial tourist will be assessed in this book.